Program Review MS in Mathematics 2016 (2016)
The Mathematics department at CSUCI and its curriculum provide a strong and flexible graduate program in mathematics. Thesis units (6) and research projects included in the program provide an opportunity for more focused and/or interdisciplinary training in pure, applied or industrialmathematics as well as mathematics education. Our Master's degree program has are well prepared to enter the workforce in technical or interdisciplinary fields or as collage levelmathematics educators, and are also ready to pursue more advanced studies in mathematics. The program produced graduates who have done well in getting employment after graduation in industry, banking or research and development units. The mathematics department's faculty are talented teachers and successful researchers and professionals. All of our hires have attained tenure and promotion when eligible. With the growth ofthe Mathematics Program has come anincreased opportunity for students to be engaged with faculty on research projects or internships in the community. Additionally, critical to the functioning of our large department, is a competent staffthat is able to handle the challenges associated to running this complex operation.